2017
DOI: 10.1007/s10948-017-4188-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Electronic and Crystal Structure in Nd 1 + x Ba 2 − x Cu 3 O 6 + δ

Abstract: In accordance with a relation between the lattice parameter c and the concentration of holes p, which has been found earlier for the YBa 2 Cu 3 O 6+ compound, we obtain the p parameter in the same manner for the solid solution Nd 1.2 Ba 1.8 Cu 3 O 6+ with substitution of Nd 3+ for Ba 2+ in barium sites. For this, structural and superconducting properties of the Nd 1.2 Ba 1.8 Cu 3 O 6+ samples stored for specified times  after quenching from annealing temperatures have been studied. The investigation shows … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…We also have found that heterovalent substitution at the cation sites next to a structural CuO 2 plane results in the following effect, which is similar to the well-known 1/8 anomaly [7][8][9]: a sharp drop in T c in the narrow δ range that corresponds to a hole concentration of 1/8 in a CuO 2 plane. In this work, we use some results from our earlier works [10,11].…”
Section: Order Disorder and Phase Transition In Condensed Systemmentioning
confidence: 99%
“…We also have found that heterovalent substitution at the cation sites next to a structural CuO 2 plane results in the following effect, which is similar to the well-known 1/8 anomaly [7][8][9]: a sharp drop in T c in the narrow δ range that corresponds to a hole concentration of 1/8 in a CuO 2 plane. In this work, we use some results from our earlier works [10,11].…”
Section: Order Disorder and Phase Transition In Condensed Systemmentioning
confidence: 99%